Morphological, physico-chemical and molecular investigations on Tuber bellonae from Basilicata-Italy - S. M. Mang; T. Zotta; I. Camele; R. Racioppi; M. D’Auria; G. L. Rana (Journal of Animal and Plant Sciences, 2017)
Morphological, physico-chemical and molecular investigations were accomplished on ascomata of Tuber bellonae from Basilicata (southern Italy) identified on the basis of their macro- and microscopic features. Tuber aestivum and T. mesentericum were used as comparative truffle species. An accurate comparison of ascospore dimensions, in 4-spored asci, a morphological character previously used to distinguish the above described truffles, was also carried out. The volatile organic compounds (VOCs) from T. bellonae were investigated by solid phase microextraction technique coupled to gas chromatography and mass spectrometry (SPME-GC-MS). The following loci were used for molecular analysis: a) the beta-tubulin gene, b) the (GTG)5 microsatellite, c) the M13 minisatellite. The ascospore volume of T. bellonae in 4-spored asci resulted significantly bigger than those of T. aestivum and T. mesentericum. Twenty-three VOCs were detected. Out of these, only 1,4-dimethoxy-2-methylbenzene, never found in T. aestivum and T. mesentericum, could be considered the main VOC marker discriminating T. bellonae. High polymorphism level was revealed in T. bellonae by both microsatellite and minisatellite markers. Finally, preliminary results on partial β-tubulin gene sequence of T. bellonae specimens suggest that T. bellonae is closely related to T. aestivum and T. mesentericum, probably holding an intermediate position between them.
Keywords: β-tubulin gene; molecular phylogeny; morphology; VOCs; Tuber bellonae